Village Head Leadership and Its Role in Enhancing Community Participation in Rural Development: Evidence from Talle Village, South Sinjai District - Makmur; Muhammad Amar; Hafizatul’ Ain; Sitti Fatimah; Nur Amin; Mochamad Nurdin; Fajaruddin (Agency Journal of Management and Business, 2026)
This study aims to analyze the role of village head leadership in enhancing community participation for village development in Talle Village, South Sinjai District. The methodology employed is a qualitative approach with data collection techniques through interviews, observations, and documentation. The findings indicate that effective village head leadership can encourage active community participation in all stages of development, from planning to implementation. The research reveals that participatory decision-making and good communication between the village head and the community are crucial for enhancing citizen engagement. However, the main challenge faced is the low attendance rate of the community in planning forums, which results in a lack of input and aspirations from the community in development planning. The conclusion of this study emphasizes the need for efforts to raise awareness and motivation among the community to become more actively involved. More sustainable and innovative strategies are required to create a conducive environment for community participation in village development.